Pengaruh Media Powtoon Interaktif terhadap Keterampilan Membaca Siswa Kelas III SDN No. 81 Sipatana - Widiantara, I Nengah; Halidu, Salma (Ideas Publishing, 2024)
The purpose of this research is to find out how effective the influence of interactive powtoon media is on students' reading skills in class III at SDN No. 81 Sipatana. This research was designed as quantitative research, using pre-experimental methods and using a one group pretest-protest design. Interactive Powtoon media is used as the independent variable, and reading skills are used as the dependent variable. Hypothesis testing in this research uses the independent t test. Based on the results of the research and discussion, the research hypothesis test shows that the calculated t value = 23.065 > t table 1.680. The significant value obtained is 0.000<0.05, with the criteria that if the sig value is smaller than 0.05 then H0 is rejected then H1 is accepted. From the two criteria above, it can be concluded that H0 is rejected and H1 is accepted, which means that there is an influence of interactive powtoon media and interactive powtoon media is effective for students' reading skills in class III at SDN No. 81 Sipatana